A General, Practical Triethylborane‐Catalyzed Reduction of Carbonyl Functions to Alcohols. Issue 42 (31st August 2015) - Peng, Dongjie; Zhang, Mintao; Huang, Zheng
Abstract A combination of the abundant and low‐cost triethylborane and sodium alkoxide generates a highly efficient catalyst for reduction of esters, as well as ketones and aldehydes, to alcohols using an inexpensive hydrosilane under mild conditions. The catalyst system exhibits excellent chemoselectivity and a high level of functional group tolerance. Mechanistic studies revealed a resting state of sodium triethylalkoxylborate that is the product of the reaction of BEt3 with sodium alkoxide. This borate species reacts with hydrosilane to form NaBEt3H, which rapidly reduces esters.